Type 2 electric vehicle charger compatible for single phase and three phase - Ming, Chiam Tat; Muhammad Ikram, Mohd Rashid (2021)
Design and development of a type 2 Electric Vehicle charger that is compatible for single phase and 3 phase that is cost effective. The Electric Vehicle charger are able to charge electric vehicle in both single phase and three phase. The Electric Vehicle charger are able to stop the charging automatically once the electric vehicle and been fully charged. The cost of the Electric Vehicle charger is low as compared to other commercial electric vehicle charger in the market. The Electric Vehicle charger is compliance to IEC62196.